Calculation Method and Application of Overhead Jumper Cable Length for Articulated Vehicles Based on the Catenary Equation - CHEN Biyang; WU Jun; LIU Tong (Chengshi guidao jiaotong yanjiu)
［Objective］ The selection of the overhead JCL (jumper cable length) for multi-marshaling urban rail transit vehicles is both complex and important. It is necessary to study the calculation method of the overhead JCL for articulated vehicles based on the catenary equation, in order to improve the calculation simplicity and accuracy. ［Method］ The principles and process involved in the calculation method of the overhead JCL for articulated vehicles based on the catenary equation are elaborated in detail; on this basis, a height calculation method of the mounting bracket installed overhead for cable crossing is proposed. In order to improve the application convenience of the method, a calculation software based on it is developed. The feasibility of the method and the software is verified in actual projects. ［Result & Conclusion］ State of the jumper cable is simulated based on catenary equation. According to the constant center distance between adjacent bogies of the articulated vehicle running along the track, the catenary equation under the limit condition is determined with reference to the minimum curve radius that the vehicle can pass through, and then JCL is calculated. The minimum JCL value is also obtained based on this. Taking into account the cable′s minimum bending radius requirement, the maximum JCL value is also obtained. The final length selection is basically to fall within this range. After determining the cable length, the height of the jumper cable′s lowest point from the installation plane can be obtained according to the catenary equation, thereby the bracket height can be obtained. The feasibility of the method is verified by actual project application effect.